Enterprise Systems Integration, Second Edition - Myerson, Judith (CRC Press, 2009)
The convergence of knowledge, technology, and human performance which comprises today's enterprise allows creative business process design. Thus, an organization can create new and innovative ways to service customers or to do business with suppliers and make itself a leader in its field. This capability relies on a successful strategy that integrates the enterprise. Enterprise Systems Integration, Second Edition continues to provide you with the business insight and the technical know-how that ensures successful systems integration. The book combines the perspectives, knowledge, and experience of more than 70 experts in the various areas that involve enterprise integration. Their expertise ranges from hands-on experience with technology and project management to the higher-level issues of business and management strategy. Each chapter examines an issue or technology relevant to today's enterprise. Collectively, these chapters span the range of enterprise computing and systems integration. Once armed with the strategy and technologies, you must successfully deploy ERP systems within budget and on time. In addition, you must be able to integrate them into the rest of the enterprise. Still, ERP software does not make up the full picture of today's enterprise. Legacy systems, e-commerce and other Web-based systems, client/server applications, networks and communications systems, data warehousing, and integrated databases enter into the mix. Enterprise Systems Integration, Second Edition paints a comprehensive picture of the technologies that comprise today's enterprise and shows you how to make them work together.